The duplicate genre - Gustavo Bernardo (Gragoatá, 2010)
The aesthetic phenomenon of metafiction calls in question the identity of fiction itself. Metafiction goes through all literary genres and duplicates the structure of each one, like the fictitious characters do with theirs authors and readers. That duplication creates a disturbing effect to the readers, as if it leads them to question themselves not only who they are but also what is reality. We will see this phenomenon in short stories written by Julio Cortázar and Mia Couto.